INDONESIAN MINISTRY OF TOURISM POLICY REGARDING HALAL TOURISM PROGRAM (An Overview of the Constructivism Approach) - Belly Rahmon; Ela Zahidiyah Tursina (UNIDA Gontor, 2020)
This article discusses the reason behind the decision from The Ministry of Tourism, Republic of Indonesia to release the Halal Tourism policy by using constructivist perspective. The Ministry has made the religious norm as the principle for the 2013 Halal Tourism Program as a response to the significant number of tourists visiting Indonesia- both domestic and foreign visitors. The Halal Tourism Program was established to fulfill the need of Muslim tourists so that they can still travel around without violating their beliefs or norms- Islamic teaching. The Ministry of Tourism has found a fact that religion is an important consideration for the tourists to make decisions on their travel destination. Using the constructivism approach and after undergoing a social process, the policy of the Halal Tourism based on Islamic norms shaped Indonesia’s identity as a country that is friendly to the needs of Muslim tourists in the international arena